New Laws of Retail Gravitation - Converse, P. D. (Journal of Marketing, 1949)
* I am indebted to Miss Janice Olbrich, Research Assistant in Marketing, and the staff of the Bureau of Economic and Business Research for statistical assistance in this study, and to my colleague, Professor Robert Mitchell, for reading and criticizing the manuscript. 1 William J. Reilly, The Law of Retail Gravitation (New York: William J. Reilly, 1931). as much trade as Champaign-Urbana. If Ba/Bb=.915 then the relative percentages can be derived by dividing .915 by 1.915. This gives 48 per cent to Bloomington and 52 per cent to Champaign-Urbana.2 A survey of consumers in Farmer City in 1942 found that Bloomington-Normal and ChampaignUrbana attracted trade from Farmer City in the proportion of 45 per cent to the former and 55 per cent to the latter. This formula is of considerable value in connection with another formula derived at the University of Illinois some years ago which determines the boundaries of a trading center's trade area. The formula (No. 2):